Wayang Krucil Panji Identitas Ideologi kultural Masyarakat Jawa Timur - Irawanto, Rudi (Universitas Negeri Makassar, 2018)
Wayang Krucil is a performing art that develops in East Java province. This puppet tells about the journey of Raden Panji Asmorobangun, Babad Majapahit and the story of Menak chronicle. Krucil puppet stories outside the Mahabharata or Ramayana epics with Hinduism theme. The phenomenon that places the ideology of wayang krucil as a representation of resistance to Hindu cultural products. The existence of wayang krucil as a representation of Hindu religion in perkembangnnya shifted into a representation of Javanese Islamic art movement or abangan Islam. The wayang krucil product as a representation of Javanese Islamic art can be seen from the use of a syncretic musical instrument with the musical instrument in performing arts of Hindu religion. The use of metal instruments is the character of abangan Islamic art. Cultural artistic art that developed in East Java represent representation of abangan culture product culture.